Relevance of documented work ability data in occupational health care – a survey for occupational health professionals - Nissinen, Sari Päivikki; Soini, Satu; Hakulinen, Hanna (Finnish Journal of eHealth and eWelfare, 2021)
In order to prolong working careers, it is essential that the signs of weak work ability are noticed, and the support of work ability are started as early as possible. The electronic patient records play a important role in this, such as how structurally the patient data has been documented. According to the Health Care Act (1326/2010), municipalities shall monitor the health and welfare of their residents. The data play a key role in this, also. The purpose of the study is to find out the importance of work ability data, its’ documentation method in electronic health records, and the suitability for national population-level monitoring data. The research material was collected in December 2019 with an e-mail survey that contained statements related to work ability data to be documented. The questionnaire was sent to 332 occupational health professionals, of whom 91 responded. The important work ability data were mental and physical performance, work disability time, patient’s and professional’s assessments of work ability, work stress factors, and a plan for returning to work. The majority of respondents used work ability data in patient care and believed the data would also be useful to other health care professionals. The most appropriate national follow-up data among work ability data were the diagnosis of the disease or the reasons for treatment, health risk, work disability time, and patient’s and professional’s assessments of work ability. The most common way on documentation of work ability data in electronic health records was free form. In utilization of the patient data, everything is depending on the documentation. The patient data must be uniformly defined, and structured, and electronic health records must enable the documentation as smoothly as possible as part of the health care professionals’ reception processes. Also, for the population-level monitoring, data should be collected from there, where it naturally arises as part of patient care.